My land and my people: the autobiography of his holiness the Dalai Lama - Tsering, Tempa (New Delhi Timeless books, 2016)
This dignified testament by a great spiritual and temporal leader, driven into exile by Communist China, is one of the most heartbreaking documents ever published. His Holiness the fourteenth Dalai Lama of Tibet relates the story of his brief, tumultuous reign climaxed by the appalling humiliation and systematic murder of his people by the Chinese. A civilized, compassionate man and a sincere reformer, he writes of the simple Tibetan life into which he was born, and among whom he, as the reincarnation of his predecessor, was discovered and declared Dalai Lama according to his country's ancient customs. During and after the invasion, the Dalai Lama appealed to the United Nations, and the International Commission of Jurists undertook a detailed study of the situation. The horror uncovered by the Commission surpassed sanity and reason, and it is detailed in these pages. My Land and My People is a tragic book. Yet, it is deeply inspiring, for the whole story is told with the gentle forgiving spirit of a Buddhist monk.
Keywords: Dalai lamas - Biography